The History of the Pioneer German Language Press of Ontario, 1835-1918 - Kalbfleisch, Herbert Karl, 1902- (Book collections on Project MUSE., 1968)
This is the story of the rise and eventual disappearance of approximately thirty German weekly newspapers during a period of about eighty years. It describes the successes and difficulties of maintaining a newspaper press directed at a minority group which was being slowly absorbed into the English-dominated pattern of Ontario.